Non‐Newtonian squashed flow simulation across Darcy‐Forchheimer sensor - Hussain, Azad; Zetoon, Rabia; Ali, Shoaib; Malik, M. Y. (Heat transfer, Asian research, 2019)
The current mathematical formulation is dedicated to investigate the Darcy‐Forchheimer boundary layer–squeezed hydromagnetic flow of a Casson fluid passing through a sensor surface. The flow phenomenon is occurring in a locally free stream under the combined sway of heat generation and thermic radiation. The energy equation is deliberated with the assistance of Cattaneo‐Christov theory rather than using Fourier's law for conduction of heat. Here, the thermic conductivity is being presumed as a function of temperature. The governing mathematical structure consists of highly nonlinear terms, so a set of regulatory parameters is being accomplished to attain the unpretentious dimensionless equations. This nondimensional structure is then treated numerically to attain the nearly converging results. The significance of substantial parameters such as magnetic factor, radiation parameter, Casson fluid parameter, heat origination, and thermal relaxation time on the flow phenomenon is estimated and presented graphically. Besides this, the factors of engineering interest like the Prandtl number and squeezed flow index with vacillating thermic conductivity have strong effects on the flow behavior of the fluid. It is observed that the magnetic effect causes an expansion in the velocity curve while a reduction is found for squeezed flow index parameter.